Does corruption discourage entrepreneurship? - Donghyun Park; Kwanho Shin (Asian Development Bank (ADB), 2022)
Although entrepreneurship plays a key role in economic development, it remains largely unknown. The reason is that it is challenging to measure entrepreneurship objectively and identify its determinants. In this paper, we analyze the effect of a particular feature of the institutional landscape, namely corruption, on entrepreneurship. It is expected that corruption discourages entrepreneurship since it undermines fair competition. We employ two proxies for entrepreneurship that are widely used in the literature: (i) nascent entrepreneurship collected from Global Entrepreneurship Monitor; and (ii) entry rate defined as the number of new firms divided by the total number of previous year's registered businesses, collected from the World Bank Group Entrepreneurship Survey. We find that better control of corruption promotes entrepreneurship. Our findings are preserved when we add other determinants of entrepreneurship which are drawn from the literature. When we use legal origins as instruments for corruption, our results remain essentially the same.
Keywords: D22; D53; D73; E02; E60; G38; 330; entrepreneurship; corruption; institution; corporate tax; legal origin